Topical Therapeutic Efficacy of Ebselen Against Multidrug-Resistant Staphylococcus aureus LT-1 Targeting Thioredoxin Reductase - Dong, Chuanjiang; Zhou, Jingxuan; Wang, Peng; Li, Tao; Zhao, Ying; Ren, Xiaoyuan; Lu, Jun; Wang, Jun; Holmgren, Arne; Zou, Lili (Frontiers in Microbiology, 2020)
As a thiol-dependent enzyme, thioredoxin reductase (TrxR) is a promising antibacterial drug target. Ebselen, an organo-selenium with well-characterized toxicology and pharmacology, was recently reported to have potent antibacterial activity against Staphylococcus aureus. In this paper, we demonstrated that ebselen has strong bactericidal activity against multidrug-resistant (MDR) S. aureus based on taking TrxR as a major target and disruption of the redox microenvironment. Further, the topical therapeutic efficacy of ebselen for staphylococcal skin infections was assessed in a rat model. Treatment with ebselen significantly reduced the bacterial load and the expression of pro-inflammatory cytokines tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and interleukin-1 beta (IL-1β) in S. aureus skin lesions; further, wound healing and pathological changes were obvious improved in ebselen-treated rats compare to controls. Finally, ebselen was found to sensitize S. aureus to curcumin, which may be due to their synergistic effects in inhibiting bacterial TrxR. Altogether, ebselen is an effective topical antibacterial agent in animal model of MDR S. aureus LT-1 skin infection. This may lay the foundation for further analysis and development of ebselen as an antibacterial agent for topical treatment of MDR staphylococcal infections.